Professionalism Workshop: Applying the Elements of Professionalism Through Scenario Learning - Paola Palma Sisto; Michael Lund; Ruth Rademacher; Ann Helms; Philip Redlich; James Sebastian; Deborah Simpson; Karen Marcdante (Association of American Medical Colleges, 2007)
Abstract Educators across the continuum of medical education seek to incorporate instruction that emphasizes the challenging yet critical elements of professionalism. Drawing on the elements of professionalism outlined by the American Board of Internal Medicine, this half-day workshop is explicitly designed to assist learners in applying the often abstract concepts of professionalism through structured discussions of real-life vignettes. The workshop is structured in three parts: an interactive lecture, a small-group facilitated discussion focused on professionalism vignettes, and a large-group debriefing allowing learners to identify themes and lessons learned and offering them options to safely report obvious unprofessional behavior. Small-group discussions center on the analysis of instructor- and learner-authored professionalism-related vignettes using the American Board of Internal Medicine professionalism terminology. We have received consistently high ratings for this workshop, with narrative comments focused on its overall quality and impact. More specifically, learners reported that the workshop merited an overall grade of high pass, and the facilitators concurred. Learners also rated their small-group facilitators very positively, with comments highlighting the opportunity to discuss professionalism issues with faculty in a nonpressured environment.